Pengaruh Informasi Laba Akuntansi Terhadap Abnormal Return pada Perusahaan yang Tergabung Dalam Indeks LQ45 - Lidya Agustina; Ferlysia Kianto (Universitas Kristen Maranatha, 2012)
The purpose of financial information test is to see how the reaction from the announcement. If the announcement have some information, the market is expected to be react at the time of announcement. This reaction can be measured with abnormal return. An announcement that have information will give abnormal return to the market. On the other hand an announcement that didn’t have information will not give abnormal return to the market. This research is purpose to examine that accounting earnings information effect to abnormal return. The sampling technique was purposive sampling method with the acquisition of the final sample of 45 companies LQ45 listed in Indonesia Stock Exchange in 2010. Data were tested using normality test, autocorrelation, outlier test and analyzed using linear regression. Result showed there is an significant effect between earnings variable toward abnormal return. In this research, periods that was used is five days before announcement until five days after the announcement.